2020
DOI: 10.9734/cjast/2020/v39i1230665
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Dependent Physical Properties of Nutmeg (Myristica fragrans) Relevant for Design of Processing Machines

Abstract: This study investigated the degree of influence of moisture content on some physical properties of nutmeg. The nutmeg seeds were subjected to six different levels of moisture content (5, 7, 9, 11, 13 and 15% db). Moisture content had a significant effect on the physical properties (p <0.05). A decrease in moisture content led to a decrease in length, width, thickness, geometric, arithmetic, square and equivalent mean diameters. Moisture content had a linear relationship with sphericity, projected and surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Nevertheless, berries shrinkage and wilt were more observable with increasing storage time. The decrease in length, width, and thickness with the decrement of moisture content was reported for ajwain seed (Singh & Meghwal, 2020), guna seed (Aviara, Gwandzang, & Haque, 1999), shea nut kernel (Aviara, Haque, & Izge, 2000), mango nut (Aviara, Iyilade, Oyeniyi, & Aremu, 2019), nutmeg (Jaiyeoba, Ogunlade, Kwanaki, & Fadele, 2020), jamun seed (Bajpai et al, 2020), and yellow passion fruit seeds (de Araujo et al, 2020).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, berries shrinkage and wilt were more observable with increasing storage time. The decrease in length, width, and thickness with the decrement of moisture content was reported for ajwain seed (Singh & Meghwal, 2020), guna seed (Aviara, Gwandzang, & Haque, 1999), shea nut kernel (Aviara, Haque, & Izge, 2000), mango nut (Aviara, Iyilade, Oyeniyi, & Aremu, 2019), nutmeg (Jaiyeoba, Ogunlade, Kwanaki, & Fadele, 2020), jamun seed (Bajpai et al, 2020), and yellow passion fruit seeds (de Araujo et al, 2020).…”
Section: Resultsmentioning
confidence: 83%
“…, shea nut kernel(Aviara, Haque, & Izge, 2000), mango nut(Aviara, Iyilade, Oyeniyi, & Aremu, 2019), nutmeg(Jaiyeoba, Ogunlade, Kwanaki, & Fadele, 2020), jamun seed(Bajpai et al, 2020), and yellow passion fruit seeds(de Araujo et al, 2020).The results of measuring seeds dimensions can be expressed using the average and standard deviation. However, these averages and standard deviations do not provide enough information to the researcher.…”
mentioning
confidence: 99%
“…This property is necessary in designing machines for the grain bulk flow and grain storage structures, especially in the design of hopper angles. Onwe et al (2020), reported a decreasing repose angle for two varieties of the investigated African star apple while Jaiyeoba et al (2020) reported the same for nutmeg seeds. The ackee seed moisture and the relationship of the angle of repose with the trends are shown in Equation ( 11 Normal and shear stresses.…”
Section: Resultsmentioning
confidence: 84%
“…Same trait holds for true density (714.3 -771.1 kg m -3 ). Unal et al (2013), Malik and Saini (2016) and Jaiyeoba et. al.…”
Section: Gravimetric Propertiesmentioning
confidence: 92%
“…Thousand seed mass was obtained by multiplying a hundred-seeds mass by 10 which was repeated Five times for each sample lot. (Milani et al, 2007;Jaiyeoba et al, 2020).…”
Section: Gravimetric Propertiesmentioning
confidence: 99%